2011
DOI: 10.1097/inf.0b013e3181f87ffe
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Childhood Diarrhea Incidence in Nicaragua Following 3 Years of Universal Infant Rotavirus Immunization

Abstract: Background-While the pentavalent rotavirus vaccine was highly efficacious against rotavirus diarrhea in clinical trials, the vaccine's effectiveness under field conditions in the developing world is unclear. In October, 2006, Nicaragua became the first developing nation to implement universal infant immunization with the pentavalent rotavirus vaccine. To assess the impact of the immunization program, we examined the incidence of diarrhea episodes between 2003 and 2009 among children in the state of León, Nicar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Nicaraguan infants are offered the vaccine at the age of 2, 4, and 6 months through the country’s Expanded Program on Immunization (EPI).Two studies conducted in Nicaraguan hospitals after the vaccine’s introduction found RV5 effectiveness was 58% and 76% against severe rotavirus diarrhea among children eligible to have received RV5 (2007 to 2008 [12], 2007 to 2009 [13]). In agreement with these studies, the incidence of diarrhea visits to health facilities had a modest decrease during the dry “rotavirus seasons” following the vaccine’s introduction and the prevalence of rotavirus diarrhea in primary care clinics declined from 14% to 4% [14, 15]. …”
Section: Introductionmentioning
confidence: 61%
“…Nicaraguan infants are offered the vaccine at the age of 2, 4, and 6 months through the country’s Expanded Program on Immunization (EPI).Two studies conducted in Nicaraguan hospitals after the vaccine’s introduction found RV5 effectiveness was 58% and 76% against severe rotavirus diarrhea among children eligible to have received RV5 (2007 to 2008 [12], 2007 to 2009 [13]). In agreement with these studies, the incidence of diarrhea visits to health facilities had a modest decrease during the dry “rotavirus seasons” following the vaccine’s introduction and the prevalence of rotavirus diarrhea in primary care clinics declined from 14% to 4% [14, 15]. …”
Section: Introductionmentioning
confidence: 61%
“…1 In addition to the benefit of ORS usage, improvement may be due to regional improvements in education and sanitation, 17 diarrheal disease or cholera control programs, 18 and the introduction of rotavirus vaccine, which has effectively reduced rotavirus-associated diarrhea incidence and pediatric-associated hospitalization. 19,20 Although these successes are to be applauded, our prevalence maps highlight areas where prevention efforts should be redoubled or new interventions undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…The final complete dataset for children 0-1 years of age included 15 studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] from six countries (United States, Brazil, Nicaragua, El Salvador, Panama, Mexico). While our initial search and coding included data for children under 5, data points for children older than 1 year of age were excluded due to inconsistencies between mortality and coverage data, and in order to include the largest number of studies possible given the variability across studies in how age groups were divided.…”
Section: Data Abstraction Synthesis and Analysismentioning
confidence: 99%